Exploring the personal burden of shoulder pain among younger people in Australia: protocol for a multicentre cohort study. Issue 7 (19th July 2018) - Ackerman, Ilana N; Page, Richard S; Fotis, Kathy; Schoch, Peter; Broughton, Nigel; Brennan-Olsen, Sharon L; Bucknill, Andrew; Cross, Emily
Abstract : Introduction: Persistent musculoskeletal conditions can impact profoundly on younger people's quality of life, psychological distress and capacity to work, as shown by previous research involving younger people with osteoarthritis. The personal impacts, in particular, work and parenting impacts, of other musculoskeletal conditions (such as persistent shoulder pain) on younger patient groups remain poorly understood. Furthermore, the personal financial burden associated with managing musculoskeletal conditions is rarely documented. This study aims to investigate well-being, work participation and productivity, shoulder-related parenting disability and out-of-pocket healthcare expenditure among younger people with shoulder pain and evaluate changes over 12 months. Methods and analysis: One hundred and fifty people aged 20–55 years with shoulder pain of more than 6 weeks' duration (excluding those with recent history of fracture or dislocation) will be recruited for this cohort study. Participants will be recruited from three major public hospitals in Victoria, Australia, following screening of orthopaedic outpatient clinics lists and referrals. Participants will be asked to complete a baseline questionnaire and 2-week healthcare costs diary, with follow-up data collected at 12 months. Patient-reported outcomes will be collected, including health-related quality of life (HRQoL), shoulder pain and function, psychological distress, shoulder-related parenting disability and work productivity. Information on sociodemographics, employment, health services utilisation and shoulder-related healthcare expenditure will also be collected. Descriptive analysis of baseline data will provide a comprehensive snapshot of the personal burden of shoulder pain. Baseline HRQoL and psychological distress data will be compared with Australian population norms to provide context around well-being. Associations between sociodemographic factors and patient-reported outcomes will be evaluated using univariate and multivariate analyses. Changes in patient-reported outcomes from baseline to 12 months will be analysed using paired t-tests. Ethics and dissemination: Ethics approval has been obtained. The study findings will be submitted to peer-reviewed journals and presented at relevant scientific meetings.